Breeding ecology of the Asian pied starling (Gracupica contra) at Jahangirnagar University campus, Bangladesh - Shoma, Shamia Farhana (Jahangirnagar University Journal of Biological Sciences, 2022)
The breeding ecology of the Asian pied starling (Gracupica contra) was studied between 2015 and 2016 at Jahangirnagar University (JU) campus to document the breeding period, nests and nest-site selection, clutch size, egg morphology, hatching and breeding success. Breeding activities of starling in JU campus started in late February and continued to early September. A total of 105 nests were recorded in two breeding seasons. The nests were loosely constructed out of straw into the shape of a dome with an entrance on the side. The average nest depth was 18±4.5 cm (n=21, range =12-29 cm) with a mean entrance diameter of 7.6±1.3 cm (n=21, range= 6-10 cm). Most of the nests (98%) were found in trees (98%), only 2% of them were found on the electric poles (2%). Overall, 17 tree species were utilized by the starlings for nesting and majority of the nests were found in Albizia procera (n=25), Gmelina arborea (n=17), and Swietenia mahagoni (n=13). The Asian pied starling nested between 3 and 18 meters (mean =10.3±3.5m) above the ground. Clutch size varied from 2 to 6 eggs with a mean size of 3.8±1.2 (n=21). Eggs were glossy blue with an average dimension of 26.6±1.6 mm×19.3±0.33 mm (n=35). Both sexes took part in incubation by rotation and fed the young. The average incubation and nestling period were 17.3±3.6 days (n=19, range=14-30) and 23±1.5 days (n=16, range=20-25), respectively. Out of the 80 eggs monitored, 63 eggs successfully hatched and 52 chicks reached their fledgeling stage, resulting in a breeding success of 65%. Jahangirnagar University J. Biol. Sci. 10(1 & 2): 49-57, 2021 (June & December)